(untitled) (ETIMA, 2025)
System restoration following a blackout event involves complex electrical and operational challenges that must comply with Commission Regulation (EU) 2017/2196 and following TSOs’ restoration codes as mandated by that Regulation. It is also mandated that TSOs review the measures of their restoration plan, including the energising restoration path from restoration service providers with black start or island operation capabilities. This paper presents a simulation-based analysis of electromagnetic and wave transients during the energisation of a hypothetical restoration route between a hydroelectric power plant (HPP) providing black-start service and a nuclear power plant (NPP) requiring auxiliary power for its systems. The study evaluates sequential and simultaneous energisation strategies using various EMTP models for the transformers. Results reveal significant insights regarding transient voltages, inrush currents, and harmonic content critical and highlight the importance of precise route modelling.